Equatorial Convergence of India and Early Cenozoic Climate Trends - D. V. Kent; G. Muttoni (2008)
India's northward flight and collision with Asia was a major driver of global tectonics in the Cenozoic and, we argue, of atmospheric CO2 concentration (pCO2) and thus global climate. Subduction of Tethyan oceanic crust with a carpet of carbonate-rich pelagic sediments deposited during transit beneath the high productivity equatorial belt resulted in a component flux of CO2 delivery to the atmosphere capable to maintain high pCO2 levels and warm climate conditions until the decarbonation factory shut down with the collision of Greater India with Asia at the Early Eocene climatic optimum at ~50 Ma. At about this time, the India continent and the highly weatherable Deccan Traps drifted into the equatorial humid belt where uptake of CO2 by efficient silicate weathering further perturbed the delicate equilibrium between CO2 input to and removal from the atmosphere towards progressively lower pCO2 levels thus marking the onset of a cooling trend over the Middle and Late Eocene that some suggest triggered the rapid expansion of Antarctic ice sheets at around the Eocene-Oligocene boundary.